NON-FUNCTIONING SPORADIC PANCREATIC NEUROENDOCRINE TUMOR IS AN INDEPENDENT RISK FACTOR FOR RECURRENCE AFTER SURGICAL TREATMENT - Estela Regina Ramos Figueira; André Luis Montagnini; Jessica Okubo; Ana Gabriela Vivarelli Fernandes; Marina Alessandra Pereira; Ulysses Ribeiro Junior; Paulo Herman; José Jukemura (ABCD: Arquivos Brasileiros de Cirurgia Digestiva)
ABSTRACT BACKGROUND: Pancreatic neuroendocrine tumors (PNETs) are uncommon and heterogeneous neoplasms, often exhibiting indolent biological behavior. Their incidence is rising, largely due to the widespread use of high-resolution imaging techniques, particularly influencing the diagnosis of sporadic non-functioning tumors, which account for up to 80% of cases. While surgical resection remains the only curative option, the impact of factors such as tumor grade, size, and type on prognosis and recurrence is still unclear. AIMS: To investigate prognostic risk factors and outcomes in patients with sporadic PNETs treated surgically. METHODS: A retrospective analysis was conducted on patients with sporadic PNETs who underwent pancreatic resection. Data were collected from medical records. RESULTS: A total of 113 patients were included: 32 with non-functioning tumors (NF-PNETs), 70 with insulinomas, and 11 with other functioning tumors (OF-PNETs). Patients with insulinoma were significantly younger, had a higher BMI, lower prevalence of comorbidities and ASA scores, and underwent significantly more pancreatic enucleations compared to patients with OF-PNET and NF-PNET. The insulinoma group had more grade I tumors, smaller tumor diameter, lower TNM staging, and lower disease recurrence rates. In univariate analysis, age, tumor type, tumor size, and TNM staging were identified as potential risk factors for tumor recurrence. In multivariate analysis, only the NF-PNET type was identified as an independent prognostic factor for disease recurrence. CONCLUSIONS: NF-PNETs are an independent prognostic risk factor for disease recurrence. This finding supports the need for closer follow-up of patients with small tumors who are selected for conservative management.